Stomatal responses to VPD utilize guard cell intracellular signaling components - Zait, Yotam; Joseph, Ariel; Assmann, Sarah M. (Frontiers in Plant Science, 2024)
Stomatal pores, vital for CO2 uptake and water loss regulation in plants, are formed by two specialized guard cells. Despite their importance, there is limited understanding of how guard cells sense and respond to changes in vapor pressure difference (VPD). This study leverages a selection of CO2 hyposensitive and abscisic acid (ABA) signaling mutants in Arabidopsis, including heterotrimeric G protein mutants and RLK (receptor-like kinases) mutants, along with a variety of canola cultivars to delve into the intracellular signaling mechanisms prompting stomatal closure in response to high VPD. Stomatal conductance response to step changes in VPD was measured using the LI-6800F gas exchange system. Our findings highlight that stomatal responses to VPD utilize intracellular signaling components. VPD hyposensitivity was particularly evident in mutants of the ht1 (HIGH LEAF TEMPERATURE1) gene, which encodes a protein kinase expressed mainly in guard cells, and in gpa1-3, a null mutant of the sole canonical heterotrimeric Gα subunit, previously implicated in stomatal signaling. Consequently, this research identifies a nexus in the intricate relationships between guard cell signal perception, stomatal conductance, environmental humidity, and CO2 levels.